First multicomponent reaction exploiting glycerol carbonate synthesis. (20th November 2018) - Costanzo, Paola; Calandruccio, Carla; Di Gioia, Maria Luisa; Nardi, Monica; Oliverio, Manuela; Procopio, Antonio
Abstract: The first example of the use of ammonia, the waste material of the bulk glycerol carbonate (GC) production, for the formation of another valuable organic molecule, a 1, 4-dihydropyridine (1, 4-DHP), by an in line two reactor system was presented. Two Q-tube reactors, one for the urea glycerolysis and the other for the Hantzsch reaction, were used, connected through a PTFE tube. Urea glycerolysis using La2 O3 as heterogeneous catalyst, under N2 pressure or in vacuum conditions, was optimized. A catalyst free and organic solvent free condition was selected to realize a Hantzsch reaction in an ecofriendly way. Glycerol carbonate and a 1, 4-dihydropyridine were synthesized in two subsequent reactions, converting wastes into added value products. The best result was that glycerol carbonate was obtained at 36% with 77% of selectivity, and at the same time the Hantzsch product was synthesized with a 75% of yield. Graphical abstract: Image 1 Highlights: Ammonia, a waste from urea glycerolysis, was recycled in a multicomponent reaction. Two Q-tube reactors were connected in line to realize an "in cascade" reaction. The first reliable way to valorize glycerol and urea for the contemporary synthesis of GC and 1, 4-DHP was reported.